2022
DOI: 10.3389/fmed.2022.961904
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of three doses of anti-SARS-CoV-2 BNT162b2 vaccine in psoriasis patients treated with biologics

Abstract: IntroductionPsoriasis has not been directly linked to a poor prognosis for COVID-19, yet immunomodulatory agents used for its management may lead to increased vulnerability to the dangerous complications of SARS-CoV-2 infection, as well as impair the effectiveness of the recently introduced vaccines. The three-dose antibody response trend and the safety of BNT162b2 mRNA vaccine in psoriasis patients treated with biologic drugs have remained under-researched.Materials and methodsForty-five psoriatic patients on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 73 publications
1
5
1
Order By: Relevance
“…The authors reported that all patients showed seroconversion after completed vaccination consisting of two doses, which fits in well with our findings (44,49). Other studies also presented similar findings (50)(51)(52)(53)(54)(55)(56). The main results of other studies that also investigated the serological response to COVID-19 vaccination in psoriasis patients are summarized in Table 4 Two of three patients without seroconversion received MTX.…”
Section: Discussionsupporting
confidence: 89%
“…The authors reported that all patients showed seroconversion after completed vaccination consisting of two doses, which fits in well with our findings (44,49). Other studies also presented similar findings (50)(51)(52)(53)(54)(55)(56). The main results of other studies that also investigated the serological response to COVID-19 vaccination in psoriasis patients are summarized in Table 4 Two of three patients without seroconversion received MTX.…”
Section: Discussionsupporting
confidence: 89%
“…There were no studies of protein subunit vaccine users that were eligible. One study was excluded from the quantitative analysis due to the use of geometric mean concentration of anti-SARS-CoV-2 spike protein IgG as a representative of the immune response ( 24 ). Table I summarizes characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…The withdraw of immunosuppressive treatment before and after receiving the vaccine was a tactic which is used to improve the efficacy of the vaccination immunity response. Currently, patients with psoriasis are recommended to receive COVID-19 vaccinations while continuing their biological treatment, and some patients may need a three-dose schedule to achieve sufficient levels of neutralizing antibodies against SARS-CoV-2 ( 31 ). Studies have shown that the second dose of BNT162b2 vaccine can effectively produce antibody responses in patients who are taking methotrexate and targeted biologics, but a lower percentage of immunosuppressed patients may have detectable T-cell responses after the second dose ( 32 ).…”
Section: Discussionmentioning
confidence: 99%